Biotransformação da diacereína por fungos e avaliação do potencial citotóxico do seu principal metabólito humano - Ferreira, Júlia Martins Ulhôa (2016)
The study of biotransformation is important in the evaluation of safety and efficacy and for developing of new drug candidates. The "microbial models of mammalian metabolism", in which microbial biotransformation is used for the purpose of predict and obtaining human metabolites, is an alternative method to the use of animals for this study. Several advantages such as lower cost, a greater quantity and variety of derivatives produced, using mild conditions of reaction and decreasing the use of toxic volatile organic solvents are observed. The aim of this study was to produce derivatives of diacerein (1,8-diacetoxy-3-carboxyanthraquinone) by biotransformation using filamentous fungi and to evaluate the cytotoxicity of the main derivatives obtained given the resurgence of interest in this class of compounds. The diacerein is an anthraquinone with a wide range of biological activities, like as anti-osteoarthritis, analgesic, anti-inflammatory, antipyretic, prevention of vascular disease, insulin resistance treatment, anticancer. Analytical methodologies have been developed for monitoring the production of derivatives by thin layer chromatography and high-performance liquid chromatography (HPLC). After screening with seventeen fungal strains, Aspergillus ochraceus ATCC 1009 and Cunninghamella echinulata ATCC 9245 were selected for incubation in semipreparative scale. Of these incubations rhein (the main human metabolite) was obtained, which was characterized using the techniques Nuclear Magnetic Resonance (NMR) 1H e 13C, High Resolution Mass Spectrometry (MS), spectrometry in the UV region and analysed by HPLC. Another derivative was obtained by incubation with Aspergillus ochraceus ATCC 1009 and characterized by MS and analyzed by HPLC being, possibly, glycosylated diacerein. The influence of the addition of cytochrome P450 inhibitor in the production of metabolites was performed and inhibited the production of rhein about 41%, which may indicate the involvement of CYP1A1 and CYP1A2 in the deacetylation reaction. The cytotoxic potential of diacerein and rhein was evaluated by the tetrazolium reduction method (MTT) assay using murine fibroblast cells 3T3 and tumor cell line B16F10 (melanoma). Both the rhein, as diacerein, have demonstrated cytotoxic potential against B16F10 cells.